(untitled) (Research, Society and Development, 2020)
The present study aims to develop and validate a reference matrix for the assessment of Exercise Physiology contents in the Physical Education undergraduation courses of the Federal Institute of Education, Science and Technology of Ceará - IFCE. This is a qualitative study. A questionnaire containing Likert-scale descriptors in terms of response was prepared. The sample consisted of five (05) professors currently working with the Exercise Physiology of IFCE, who were the expert judges for content validation via the Content Validity Index (CVI). Regarding the content validity, the results showed that based on the descriptors constructed and presented to the judges, 07 were not modified, 11 were adjusted (following the request of the evaluating judges), however all had acceptable CVI, 01 was excluded and 04 were included. Thus, the final version of the Reference Matrix for the evaluation of Exercise Physiology contents is composed of 22 descriptors. One may conclude that it was possible to develop and validate a reference matrix for the evaluation of Exercise Physiology content in Physical Education undergraduate courses.